ISSUES OF INTRODUCING ISLAMIC FINANCE SERVICES IN UZBEKISTAN (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article analyzes the issues of introducing Islamic finance in the Republic of Uzbekistan. It highlights the need to diversify the country's financial system, the basic principles of Islamic finance and its advantages. It also discusses the main obstacles to the development of Islamic finance, including the lack of a legal and regulatory framework, the shortage of qualified specialists, and the population's insufficient awareness of Islamic finance. The author also provides recommendations on the infrastructure and products necessary for the development of Islamic finance. This article serves as an in-depth study of the opportunities and limitations of Islamic finance in the conditions of Uzbekistan.